2019
DOI: 10.1111/odi.13168
|View full text |Cite
|
Sign up to set email alerts
|

Early growth response 1 reduction in peripheral blood involving condylar subchondral bone loss

Abstract: Objectives To detect whether early growth response 1 (EGR1) in peripheral blood leucocytes (PBLs) indicates temporomandibular joint (TMJ) osteoarthritis (OA) lesions. Materials and Methods Egr1 mRNA expression levels in PBLs were detected in eight malocclusion patients without temporomandibular disorder (TMD) signs and 16 malocclusion patients with clinical TMD signs with (eight) or without (eight) imaging signs of TMJ OA. Twelve 6‐week‐old rats were randomized to a control group and a unilateral anterior cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Some authors have attempted to highlight markers that can be used to predict the development of TMJOA. Zhang et al showed that early growth response 1 (Egr1) reduction in peripheral blood leukocytes potentially indicates early-stage subchondral bone OA [ 57 ]. Reed et al hypothesized that depletion of type VI collagen may be an early biomarker for the transition from early to end stage TMJOA [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have attempted to highlight markers that can be used to predict the development of TMJOA. Zhang et al showed that early growth response 1 (Egr1) reduction in peripheral blood leukocytes potentially indicates early-stage subchondral bone OA [ 57 ]. Reed et al hypothesized that depletion of type VI collagen may be an early biomarker for the transition from early to end stage TMJOA [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various animal models exist for the study of TMJOA using surgical (such as discectomy), mechanical (such as unilateral anterior cross-bite), chemical (such as intra-articular injections of monosodium iodoacetate or complete Freund’s adjuvant), and genetic techniques (such as Cre-recombination and knockout) [ 5 , 8 , 13 , 41 , 43 , 44 , 51 ]. The most commonly used techniques were discectomy [ 11 , 43 , 45 , 53 ], unilateral anterior cross-bite [ 36 , 38 , 44 , 46 , 54 , 57 ], intra-articular injections of monosodium iodoacetate [ 26 , 37 ], complete Freund’s adjuvant [ 41 , 48 ], and genetic techniques [ 8 , 49 , 51 ]. However, no gold standard animal model exists [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 , 22 The subchondral bone of the condyle is located under the cartilage, and stress is transmitted from the cartilage to bone buffers to maintain the stability and shape of the TMJ. 23 , 24 Abnormal bone remodelling during the development of OA results in subchondral bone mass and structure changes. 25 Bone remodelling, a process that couples bone formation due to osteoblasts and bone absorption due to osteoclasts, plays a central role in bone homeostasis in OA.…”
Section: Discussionmentioning
confidence: 99%
“…EGR1 belongs to the EGR family of C2H2-type zinc-finger protein [ 30 ]. EGR1 could accelerate cartilage hyper proliferation and degeneration by regulating KLF5 expression and β -catenin signaling pathway [ 31 ]. Specificity protein 1(SP1), as a C2H2-type zinc-finger transcription factor, inhibits the proliferation of chondrocytes and promotes the apoptosis of chondrocytes by binding with miR-145 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%